Using community‐based participatory research to address STI/HIV disparities and social determinants of health among young GBMSM and transgender women of colour in North Carolina, USA. (28th December 2020) - Mann‐Jackson, Lilli; Alonzo, Jorge; Garcia, Manuel; Trent, Scott; Bell, Jonathan; Horridge, Danielle N.; Rhodes, Scott D.
Abstract: Sexually transmitted infections (STIs) and HIV disproportionately affect young persons; gay, bisexual and other men who have sex with men (GBMSM) and transgender women; persons of colour; and the U.S. South. Complex issues contribute to these high STI/HIV rates. Our community‐based participatory research (CBPR) partnership conducted a community‐driven needs assessment to inform an intervention addressing STI/HIV disparities and related social determinants of health (SDH) among young GBMSM and transgender women of colour in a high‐incidence STI/HIV community in North Carolina. In 2018, in‐depth interviews were conducted with 21 community members and 29 community organisation representatives to explore needs, priorities and assets. Interview data were analysed using constant comparison, an approach to grounded theory, and an empowerment theory‐based planning process was used to develop multilevel intervention strategies based on findings. Thirteen themes emerged from the interviews that were organised into five domains: health (e.g., limited health services use; need for lesbian, gay, bisexual and transgender [LGBT]‐friendly providers; prioritisation of mental health and gender transition and limited knowledge of and access to pre‐exposure prophylaxis [PrEP] for HIV); employment (e.g., employment as a priority and relying on sex work to 'make ends meet'); education (e.g., barriers to education and needs for training to improve employment opportunities); social support (e.g., few welcoming activities and groups; strong informal support networks and little interaction between GBMSM and transgender women) and discrimination (e.g., frequent experiences of discrimination and the impact of frontline staff on services use). Three strategies – community‐based peer navigation, use of social media, and anti‐discrimination trainings for organisations – were identified and integrated into a new intervention known as Impact Triad . CBPR was successfully applied to identify needs, priorities and assets and develop a multilevel intervention focused on health disparities and SDH among young GBMSM and transgender women of colour in the U.S. South.